An analysis of organizational commitment in nonprofit organizations using partial least squares structural equation modeling - Aguiling, Maria Adiel H. (Animo Repository, 2020)
Social service nonprofit organizations (NPOs) are sustained when employees are committed. The purpose of this research is to analyze the relationship of the exogenous latent variables or identified predictors of employees’ commitment to the organization, with the endogenous latent variable of organizational commitment; and the relationship between the exogenous and endogenous latent variables with its indicators, using Partial Least Squares Structural Equation Modeling (PLS-SEM). Using this data analysis method, the model fit is acceptable. Discriminant and convergent validity as well as internal consistency reliability are confirmed. Two hundred three employees in social service nonprofits in the Philippines, participated in the study. The results show that there is an extremely strong evidence that job satisfaction is a predictor of organizational commitment. Likewise, there is an extremely strong evidence that attitudes toward NPOs is a predictor of organizational commitment. There is an extremely strong evidence that tenure affects the strength of relations between attitudes toward NPOs and organizational commitment. Altruistic behavior, however, does not manifest any evidence of a relationship with organizational commitment. Moreover, there is no evidence that tenure moderates the relationship between altruism and organizational commitment. Similarly, there is no evidence that tenure affects the direction of the relations between job satisfaction and organizational commitment. Nonprofits benefit from a leader who is technically competent and who can propel employees’ satisfaction with their job. The research gives insight on nonprofits as a brand, and the need for nonprofits to deliver their promise and maintain a good image of the sector. It recommends further study on how the national accrediting body of NPOs can improve the sustainability and integrity of nonprofits. Research on job satisfaction, attitudes toward nonprofits, and organizational commitment in NPOs with a social mission are valuable in order to stir the interest and collaboration of local and foreign companies, inclusive of global business.